2023
DOI: 10.3390/pharmaceutics15071993
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Drug Delivery: Highly Thiolated κ-Carrageenan as Mucoadhesive Excipient

Abstract: Aim: This study aims to design a novel thiolated κ-carrageenan (κ-CA-SH) and evaluate its potential as an excipient for the design of mucoadhesive drug delivery systems. Methods: Native κ-carrageenan (κ-CA) was thiolated with phosphorous pentasulfide in sulfolane and characterized via 1H NMR, FTIR, as well as Ellman’s test. Cytotoxicity was assessed via resazurin assay. In vitro release of the model drug, benzydamine hydrochloride, was determined. Tensile and mucosal residence time studies were performed on bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Pharmaceutics 2024, 16, 626 3 of 22 in periodontal regeneration [26], and in oral cancer [27][28][29]. The third type of reporting on the transdermal and transmucosal systems used in oral pathology are particularly focused on the various possibilities of improving absorption, whether we refer to it as a question of excipients with an amplifying effect [15,28,30] or to that of physical amplifiers (microneedles, iontophoresis, sonophoresis, and electrophoresis) [31][32][33][34]. Unlike the previously mentioned works, our work presents a more complex approach, considering a varied oral pathology as well as various types of controlled release systems that address these pathologies.…”
Section: Principles Of Release Of Active Substances Into the Oral Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutics 2024, 16, 626 3 of 22 in periodontal regeneration [26], and in oral cancer [27][28][29]. The third type of reporting on the transdermal and transmucosal systems used in oral pathology are particularly focused on the various possibilities of improving absorption, whether we refer to it as a question of excipients with an amplifying effect [15,28,30] or to that of physical amplifiers (microneedles, iontophoresis, sonophoresis, and electrophoresis) [31][32][33][34]. Unlike the previously mentioned works, our work presents a more complex approach, considering a varied oral pathology as well as various types of controlled release systems that address these pathologies.…”
Section: Principles Of Release Of Active Substances Into the Oral Cavitymentioning
confidence: 99%
“…The oral mucosa, by its large surface area, is an excellent interface for mucoadhesive systems (tablets, patches, films, gels, wafers, gums) that can be applied either on the oral mucosa, the sublingual mucosa, or even on the gum. The most commonly used form refers to adhesive tablets (e.g., intraoral metronidazole tablets) [30,68,69].…”
Section: Intraoral Mucoadhesive Systemsmentioning
confidence: 99%
“…In general, thiolated biopolymers provide higher mucoadhesion and drug residence time compared to native polymers, thereby increasing drug bioavailability. Thiolated biopolymers also inhibit some enzymes, thereby increasing drug stability, as well as providing controlled drug release and increasing cell permeability [145,146]. The most commonly used thiolating agents are thioglycolic acid, thiourea, 4-aminothiophenol, L-cysteine and Trout's reagent (2-iminothiolane).…”
Section: Thiolated Biopolymers (Thiomers)mentioning
confidence: 99%
“…At the molecular level, the chemical structures of already-existing mucoadhesive polymers could be improved. Kali et al [209] suggested the incorporation of thiol groups into polymers in order to enhance mucoadhesion. As a result of the formation of disulfide bonds with cysteine-rich regions in mucins, polycarbophil-cysteine conjugates exhibit a great deal of mucoadhesion.…”
Section: Mucoadhesive Biomaterialsmentioning
confidence: 99%